Analysis of Unidirectional Absorption in a Defective Superconducting Photonic Crystal - Tsung-Wen Chang; Chih-Hsi Huang; Da Jun Hou; Chien-Jang Wu; De-Xin Chen (IEEE Photonics Journal, 2017)
Terahertz unidirectional resonant absorption in a finite one-dimensional defective superconducting photonic crystal is theoretically investigated. We consider an asymmetric photonic crystal (AB)ND(BA) M, where A is a dielectric, B is a superconductor, D is the dielectric defect, and N, M are the stack numbers, respectively. At $N \ne M$ , it is found that the resonant absorption for the structure exhibits the unidirectional property. The unidirectional resonant absorption points increase as the difference between N and M increases. We also investigate the unidirectional property as a function of angle of incidence. The results show that the unidirectional absorption is nearly independent of the polarization at a given angle of incidence. The proposed structure can be used to design a polarization-independent optical device which may be technically used in superconducting photonics.